The NHR1-1 of Prs1 and the pentameric motif 284KKCPK288 of Prs3 permit multi-functionality of the PRPP synthetase in Saccharomyces cerevisiae. Issue 2 (11th January 2019) - Sauvaget, Maëlle; Hutton, Fraser; Coull, Robert; Vavassori, Stefano; Wang, Ke; Reznik, Aleksandra; Chyker, Tatsiana; Newfield, Chelsea G; Euston, Eloise; Benary, Gerrit; Schweizer, Lilian M; Schweizer, Michael
Abstract: The five-membered PRS gene family of Saccharomyces cerevisiae is an example of gene duplication allowing the acquisition of novel functions. Each of the five Prs polypeptides is theoretically capable of synthesising PRPP but at least one of the following heterodimers is required for survival: Prs1/Prs3, Prs2/Prs5 and Prs4/Prs5. Prs3 contains a pentameric motif 284 KKCPK288 found only in nuclear proteins. Deletion of 284 KKCPK288 destabilises the Prs1/Prs3 complex resulting in a cascade of events, including reduction in PRPP synthetase activity and altered cell wall integrity (CWI) as measured by caffeine sensitivity and Rlm1 expression. Prs3 also interacts with the kinetochore-associated protein, Nuf2. Following the possibility of 284 KKCPK288 -mediated transport of the Prs1/Prs3 complex to the nucleus, it may interact with Nuf2 and phosphorylated Slt2 permitting activation of Rlm1. This scenario explains the breakdown of CWI encountered in mutants lacking PRS3 or deleted for 284 KKCPK288 . However, removal of NHR1–1 from Prs1 does not disrupt the Prs1/Prs3 interaction as shown by increased PRPP synthetase activity. This is evidence for the separation of the two metabolic functions of the PRPP-synthesising machinery: provision of PRPP and maintenance of CWI and is an example of evolutionary development when multiple copies of a gene were present in the ancestral organism. Abstract : Manipulation of the Saccharomyces cerevisiae Prs1/Prs3 complex identifies three different functions: PRPP synthesis, CWI maintenance and intracellular transport.